PENDAMPINGAN PUS DALAM PENGGUNAAN MKJP SEBAGAI UPAYA MENEKAN UNMET NEED DI KAMPUNG KB - Sutrisminah, Emi; Aisyaroh, Noveri (Stikes Yarsi Mataram, 2025)
The population in Indonesia continues to increase until in 2018 it reached 263 million people. Unmet need for family planning is one of the obstacles to the management of family planning programmes in Indonesia that requires continuous handling. Unmet need has a high potential for unwanted pregnancies (KTD). Sumberrahayu Village is a small village in the Limbangan sub-district that has 137 PUS. Of the 137 PUS, only 90 PUS have family planning, and 47 PUS do not have family planning. Based on these problems, this community service aims to convert unmet need MHJP centres into MHJP family planning acceptors. The service began with identification of PUS, pretest of PUS knowledge about MHJP, followed by counselling with ABPK media, post-test of PUS knowledge, installation of MHJP alkon. All unmet need PUS were willing to become MHJP acceptors, namely the installation of MKJP contraceptives. After the installation of MHJP, all PUS did not experience any side effects after the installation of MKJP contraceptives. It is expected that health workers will increase intensive and maximum counselling to PUS unmet need.